2014
DOI: 10.4172/2329-9002.1000131
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Markers in Phylogenetic Studies-A Review

Abstract: Uses of molecular markers in the phylogenetic studies of various organisms have become increasingly important in recent times. This review gives an overview of different molecular markers employed by researchers for the purpose of phylogenetic studies. Availability of fast DNA sequencing techniques along with the development of robust statistical analysis methods, provided a new momentum to this field. In this context, utility of different nuclear encoded genes (like 16S rRNA, 5S rRNA, 28S rRNA) mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 73 publications
1
60
0
3
Order By: Relevance
“…For example, Mengual et al (2006) found variability in a dinucleotide repeat region, AT (1-5) between Spanish M. albifrons specimens and interpreted it as intraspecific. In contrast to the variability of COI and ITS2 sequences, the 28S rRNA gene sequences are typically more conservative and most often do not show a significant divergence between closely related species (Mengual et al, 2006;Patwardhan et al, 2014) which has also been shown in the M. caerulescens complex. A total of 13 sequences of the 28S rRNA gene of M. caerulescens complex were analyzed.…”
Section: Molecular Evidencementioning
confidence: 99%
“…For example, Mengual et al (2006) found variability in a dinucleotide repeat region, AT (1-5) between Spanish M. albifrons specimens and interpreted it as intraspecific. In contrast to the variability of COI and ITS2 sequences, the 28S rRNA gene sequences are typically more conservative and most often do not show a significant divergence between closely related species (Mengual et al, 2006;Patwardhan et al, 2014) which has also been shown in the M. caerulescens complex. A total of 13 sequences of the 28S rRNA gene of M. caerulescens complex were analyzed.…”
Section: Molecular Evidencementioning
confidence: 99%
“…Phylogeny is the history of descent of a group of taxa such as species from their common ancestors including in a study on the basis of their relationships so groupings indicates the degree of genetic similarities and dissimilarities among them (Patwardhan et al, 2014).…”
Section: Taxa Identification Phylogenetic Relationship and Identificmentioning
confidence: 99%
“…Random amplified polymorphic DNA (RAPD) enables a survey of different loci simultaneously [9]. RAPD markers have been extensively used to analyse different aspects of plant genomes, including evaluation of genetic diversity [10], construction of genetic maps [11], marker-assisted selection [12], identification of progenies of cross pollination [13], population structure [14] and also phylogeny studies of different related species and genera [15]. These multilocus markers are not only simple, fast and sensitive, but also universal, which makes them useful for comparing different related genera and species at DNA level.…”
Section: Introductionmentioning
confidence: 99%